Role of the Forkhead Transcription Factors Fd4 and Fd5 During Drosophila Leg Development - Ruiz-Losada, Mireya; Pérez-Reyes, Cristian; Estella, Carlos (Frontiers in Cell and Developmental Biology, 2021)
Appendage development requires the coordinated function of signaling pathways and transcription factors to pattern the leg along the three main axes: the antero-posterior (AP), proximo-distal (PD), and dorso-ventral (DV). The Drosophila leg DV axis is organized by two morphogens, Decapentaplegic (Dpp), and Wingless (Wg), which direct dorsal and ventral cell fates, respectively. However, how these signals regulate the differential expression of its target genes is mostly unknown. In this work, we found that two members of the Drosophila forkhead family of transcription factors, Fd4 and Fd5 (also known as fd96Ca and fd96Cb), are identically expressed in the ventro-lateral domain of the leg imaginal disc in response to Dpp signaling. Here, we analyze the expression regulation and function of these genes during leg development. We have generated specific mutant alleles for each gene and a double fd4/fd5 mutant chromosome to study their function during development. We highlight the redundant role of the fd4/fd5 genes during the formation of the sex comb, a male specific structure that appears in the ventro-lateral domain of the prothoracic leg.